Comparative study of some species of the genus Acer L. in the Hirkan flora using dendrochronological methods - Agamalieva Aydan Gahraman; Mehrelieva Hokume Ilham; Mammadova Shalala Abuzer; Alieva Khadija Hezi; Esli Ilaida Aga Aleskerova (BIO Web of Conferences)
Recently, due to global climate change and unregulated human economic activities, biodiversity has significantly degraded, which has led to changes and reductions in the ranges of species. Observations show that there is no comprehensive conservation strategy to protect certain regions where rare and endangered species of woody plants of the flora of Azerbaijan live. With the increase in the number of rare species and the decrease in the number of endangered plants, identifying the causes of these problems and preventing their further degradation is an urgent issue for both government agencies and scientific institutions. The main objective of this scientific study is to conduct a biometric and dendrochronological analysis of the processes occurring in the populations of rare species of the Hirkan flora. The study also includes monitoring the areas where rare and endangered species are found and developing action plans to assess and protect these ecosystems. The article presents studies conducted on samples of old species Acer hyrcanum and Acer mono, selected from the flora of Hyrcanus. Comparative analysis of the species was carried out using dendrochronological methods. Modern equipment was used to determine the age of species, study the dynamics of their development and assess the impact of environmental factors on them. As is known, woody plants experience radial and vertical growth, forming annual rings, although there are exceptions due to a number of complex factors. Among them, climatic conditions, habitat features, as well as genetic and age characteristics of plants play a particularly important role.